The Description of Health Literacy, Knowledge, and Skills of Elderly People with Diabetes Mellitus Using Insulin Injections at Public Health Centers in Makassar City - Akbar, Akbar; Jafar, Nuurhidayat (Indonesian Contemporary Nursing Journal (ICON Journal), 2025)
Objective: To assess the health literacy, knowledge, and skills of older adults with Diabetes Mellitus using insulin injections at Public health centers in Makassar City in 2024. Methods: This study is a quantitative research with a descriptive design using a cross-sectional approach. The sample selection employed non-probability sampling, expressly incidental sampling, involving 200 elderly individuals with Diabetes Mellitus who use insulin injections. Data was collected using the HLS-EU-SQ10-IDN and a knowledge and skills questionnaire on insulin use. The questionnaires were adapted into Indonesian and tested for validity and reliability. Results: The study found that out of 200 elderly respondents, 97.0% were aged 60-74 years, with a mean age of (65.70). The majority were female (59.0%), retirees (44.5%), and had completed high school (49.5%). About 67.0% had suffered from Diabetes Mellitus for 5 years or more, with a mean of 7.17 years. Half of the respondents (50.0%) used Novorapid FlexPen® insulin, while 70.0% were on the additional antidiabetic drug Metformin. Blood glucose levels (GDP) were in the prediabetic range (100-125 mg/dl) for 50.5% of respondents, with a mean of 142.57 mg/dl. Most had comorbid hypertension (80.5%) and a normal BMI (56.0%). The health literacy level was sufficient for (70.5%) of respondents, with 98% showing good knowledge and (93.5%) demonstrating good skills. Conclusion: Most showed sufficient health literacy and demonstrated good knowledge and skills. These findings highlight the importance of comprehensive health support for elderly individuals with diabetes.